2019
DOI: 10.1523/eneuro.0425-17.2019
|View full text |Cite
|
Sign up to set email alerts
|

The VWFA Is the Home of Orthographic Learning When Houses Are Used as Letters

Abstract: Learning to read specializes a portion of the left mid-fusiform cortex for printed word recognition, the putative visual word form area (VWFA). This study examined whether a VWFA specialized for English is sufficiently malleable to support learning a perceptually atypical second writing system. The study utilized an artificial orthography, HouseFont, in which house images represent English phonemes. House images elicit category-biased activation in a spatially distinct brain region, the so-called parahippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Developmental studies indicate that the print-sensitive response of the VWFA shows a rapid development in the first few months and years of learning to read 26 33 and that it is initiated by grapheme-phoneme correspondence training in children 26 , 29 , 34 and adults 35 , 36 . The location of the emerging print-sensitive area within the vOT seems constrained by its established connectivity to language regions long before children learn to read at school 13 , 37 and develops in cortical patches with only weak specialization 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Developmental studies indicate that the print-sensitive response of the VWFA shows a rapid development in the first few months and years of learning to read 26 33 and that it is initiated by grapheme-phoneme correspondence training in children 26 , 29 , 34 and adults 35 , 36 . The location of the emerging print-sensitive area within the vOT seems constrained by its established connectivity to language regions long before children learn to read at school 13 , 37 and develops in cortical patches with only weak specialization 29 .…”
Section: Introductionmentioning
confidence: 99%
“…A dorsal pathway underpins phonologically mediated reading, and a ventral pathway underpins direct access to meaning from print. The Visual Word Form Area (VWFA) is used "as a word letterbox" (Dehaene 2010) but is also used for other purposes (Vogel 2012, Moore 2014, Martin 2019. Many further cortical areas will be involved when meaningful reading occurs, for example reading stories with an emotional impact, and the brain engages with that meaning in its social context.…”
Section: Resultsmentioning
confidence: 99%
“…(Hannagan et al, 2015;Hasson et al, 2002;Szwed et al, 2011). However, this view fell in disfavor when it was found that, when participants were trained to "read" words written in unusual fonts made of faces or houses, those non-letterlike reading stimuli continue to activate the VWFA during reading (Martin et al, 2019;Moore et al, 2014). More recently it was suggested that the connectivity to other brain regions might be an important factor (Hannagan et al, 2015;Saygin et al, 2016).…”
Section: Functional Connectivity Of the Vwfa And Of The Ffamentioning
confidence: 99%